Genes driving potato tuber initiation and growth: identification based on transcriptional changes using the POCI array - Kloosterman, Bjorn; De Koeyer, David; Griffiths, Rebecca; Flinn, Barry; Steuernagel, Burkhard; Scholz, Uwe; Sonnewald, Sophia; Sonnewald, Uwe; Bryan, Glenn J.; Prat, Salome; Banfalvi, Zsofia; Hammond, John P.; et al. (Functional & Integrative Genomics, 2008)
The increasing amount of available expressed gene sequence data makes whole-transcriptome analysis of certain crop species possible. Potato currently has the second largest number of publicly available expressed sequence tag (EST) sequences among the Solanaceae. Most of these ESTs, plus other proprietary sequences, were combined and used to generate a unigene assembly. The set of 246,182 sequences produced 46,345 unigenes, which were used to design a 44K 60-mer oligo array (Potato Oligo Chip Initiative: POCI). In this study, we attempt to identify genes controlling and driving the process of tuber initiation and growth by implementing large-scale transcriptional changes using the newly developed POCI array. Major gene expression profiles could be identified exhibiting differential expression at key developmental stages. These profiles were associated with functional roles in cell division and growth. A subset of genes involved in the regulation of the cell cycle, based on their Gene Ontology classification, exhibit a clear transient upregulation at tuber onset indicating increased cell division during these stages. The POCI array allows the study of potato gene expression on a much broader level than previously possible and will greatly enhance analysis of transcriptional control mechanisms in a wide range of potato research areas. POCI sequence and annotation data are publicly available through the POCI database (http://pgrc.ipk-gatersleben.de/poci).
Keywords: potato unigene; oligo array; tuber development; expression profiling